Akulturasi Budaya Batak Angkola dan Batak Toba Dalam Upacara Adat Perkawinan di Desa Padang Parsadaan, Kecamatan Pangaribuan - Harahap, Betsaida; Lase, Sudirman; Boni Firmando, Harisan; Sitopu, Elisamark; T.J Hutagalung, Bambang (Green Publisher Indonesia, 2024)
Traditional marriage ceremonies in the Bataknese community, especially Batak Angkola and Batak Toba have very unique rules and traditions. Exogamus marriage in Batak Toba forbid marriages between the same and as well as Batak Angkola which applies a patrilineal system with the “jujur” custom involving the payment of sinamot from the man to the woman,the main reason of marriage for the society of Batak Angkola and Batak Toba are to reach prosperty (hamoraon) owning many descendants (hagabeon) and obtaining honor (hasangapon). Acculturation is the process where elements from two or more diff cultural grups interact and live together then integrate into their own culture without losing their original cultural identity. In the village Padang Parsadaan, cultural acculturation happens between the culture Batak Angkola and Batak Toba in the traditional marriage ceremonies, initially society has resistance to this acculturation, but after a long disscussion, cultural integration started to be accepted and applied. This acculturation process arms to create social harmony but still maintaining their own cultural identity. This observation uses descriptive qualitive method with analytical approach for understanding the process and impact of acculturation. The result of this observation shows that acculturation enrich the social life and societies culture and increasing the intercultural tolerance in the village Padang Parsadaan. Acculturation also helps younger generation undestand and adapt to changes, however acculturation needs effort and support together from society and traditional leaders to over obstacles and ensuring the continuation of cultural acculturation especially traditional marriage ceremonies.